Antinociceptive activity of the essential oil of Zingiber zerumbet. - Sulaiman, Mohd Roslan; Tengku Mohamad, Tengku Azam Shah; Shaik Mossadeq, Wan Mastura; Moin, Saidi; Mohd Yusoff, Mazina; Mokhtar, Ahmad Fauzi; Zakaria, Zainul Amiruddin; Israf Ali, Daud Ahmad; Lajis, Nordin (Georg Thieme Verlag, 2010)
In the present study, the rhizome essential oil from Zingiber zerumbet (Zingiberaceae) was evaluated for antinociceptive activity using chemical and thermal models of nociception, namely, the acetic acid-induced abdominal writhing test, the hot-plate test and the formalin-induced paw licking test. It was demonstrated that intraperitoneal administration of the essential oil of Z. zerumbet (EOZZ) at the doses of 30, 100 and 300mg/kg produced significant dose-dependent inhibition of acetic acid-induced abdominal writhing, comparable to that of obtained with acetylsalicylic acid (100mg/kg). At the same doses, the EOZZ produced significant dose-dependent increases in the latency time in the hot-plate test with respect to controls, and in the formalin-induced paw licking test, the EOZZ also significantly reduced the painful stimulus in both neurogenic and inflammatory phase of the test. In addition, the antinociceptive effect of the EOZZ in the formalin-induced paw licking test as well as hot-plate test was reversed by the nonselective opioid receptor antagonist, naloxone suggesting that the opioid system was involved in its analgesic mechanism of action. On the basis of these data, we concluded that the EOZZ possessed both central and peripheral antinociceptive activities which justifying its popular folkloric use to relieve some pain conditions.